2019
DOI: 10.1111/btp.12666
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in the influence of forest succession on caterpillar communities: A long‐term study in a tropical dry forest 

Abstract: Forest succession can influence herbivore communities through changes in host availability, plant quality, microclimate, canopy structure complexity and predator abundance. It is not well known, however, if such influence is constant across years.Caterpillars have been reported to be particularly susceptible to changes in plant community composition across forest succession, as most species are specialists and rely on the presence of their hosts. Nevertheless, in the case of tropical dry forests, plant species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Because sampling bias is an important concern in the majority of ecological studies (34), we tested whether our results would be a↵ected by the sampling e↵ort in reporting species, by an incomplete plant VOC profile, and by sampling the interaction network in a di↵erent year or place. We found that all our results were qualitatively equivalent when using sub-samples from the whole dataset (illustrating the scalability of our findings), changing the VOC profile from 31 to 52 by including potential undefined biogenic VOCs, and using information of plant-herbivore interaction networks from previous years (from 2007-2017) (35). Ref.…”
supporting
confidence: 57%
“…Because sampling bias is an important concern in the majority of ecological studies (34), we tested whether our results would be a↵ected by the sampling e↵ort in reporting species, by an incomplete plant VOC profile, and by sampling the interaction network in a di↵erent year or place. We found that all our results were qualitatively equivalent when using sub-samples from the whole dataset (illustrating the scalability of our findings), changing the VOC profile from 31 to 52 by including potential undefined biogenic VOCs, and using information of plant-herbivore interaction networks from previous years (from 2007-2017) (35). Ref.…”
supporting
confidence: 57%
“…However, we must acknowledge the limitations of the temporal scale of our data, with a dataset of only two years. Studies assessing the impact of different stages of succession conducted over longer temporal periods would give a more precise picture of the impact of community dynamics of ant communities (e.g., Rozendaal et al, 2019, for plants, and Novais et al., 2018, and Boege et al., 2019, for other insects).…”
Section: Discussionmentioning
confidence: 99%
“…Among tropical forests, dry forests are highly threatened ecosystems, with a constant increase in forest gaps due to anthropogenic activities in the last decades, and the majority of such habitats consist of a mosaic of forests in different stages of vegetation succession (Quesada et al., 2009). Importantly, forest succession drives changes in the insect community structure in different ecosystems (Boege et al., 2019; Bongers et al, 2004; Jeffries et al., 2006). In particular, variation in ant communities across forest succession has been associated with changes in forest complexity and heterogeneity of micro‐environmental conditions (Klimes et al., 2012; Marques et al., 2017) but can result in unpredictable patterns in the canopy (Antoniazzi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specimens of Lepidoptera were deposited in the Lepidoptera collection (ECO‐CH‐L) and Hymenoptera and Diptera in the Arthropod Collection (ECO‐CH‐AR), both collections of the Zoological Museum at ECOSUR. To assist in species delineation and identification of morphospecies, morphology‐based taxonomy and DNA sequences were both used following Boege et al (2019). We used CO1 sequences (Hebert et al, 2003) for comparisons with libraries available in the Barcode of Life Data (BOLD) system following Ratnasingham and Hebert (2013).…”
Section: Methodsmentioning
confidence: 99%
“…All Piper species were identified by EJT, and determinations of individuals from the plots were verified against the collections in the Herbarium at ECOSUR (CIQR). Caterpillars were photographed in the field or laboratory, and larvae and adults were identified to genus or species by CP and LD, and using online resources (Janzen & Hallwachs, 2012; Boege et al (2019). We used CO1 sequences (Hebert et al, 2003) for comparisons with libraries available in the Barcode of Life Data (BOLD) system following Ratnasingham and Hebert (2013).…”
Section: Sampling Piper-caterpillar-parasitoid Interactionsmentioning
confidence: 99%